“Análisis y aplicación de la NIC 2 de inventarios en una empresa importadora y comercializadora de artículos de viaje y afines caso “comercial Equipaggio Cía. Ltda.”. - Cárdenas Gaibor, Ericka Melissa (2013)
This thesis focuses on the International Accounting Standard IAS 2 " INVENTORIES", in which this standard defines inventories as assets retained for sale in the ordinary course of business activities , or those who have past a production process and are ready for sale . It has been taken as a thesis project Comercial Equipaggio Cia. Ltda. as it has some shortcomings because it does have an organizational culture in its mission, vision and principles , however the objectives and short-term goals are set by planning based on budgets . The administration has no plans of action and strategies to solve business problems or take advantage of their strengths . The staff of the company does not know its functions and has clearly defined responsibilities , so it is a complication when applying IAS 's.